Claiming the Right to be Forgotten (Economic and political weekly, 2022)
[...]if the data subject has withheld their consent because there subsists no other valid reason or the data subject has objected and there are no overriding reasonable reasons for the processing or whether, in order to conform with a contractual requirement under European Union law, deletion is obligatory. The Karnataka High Court, in a case decided on 4 January 2018, recognised the “RTBF” explicitly, though in a limited sense, and observed that the Information Technology (Reasonable Security Practices and Procedures and Sensitive Personal Data or Information) Rules, 2011 was the first legal framework that recognised the need to protect the privacy of personal data but failed to capture the issue of the RTBF. The RTBF has not been formally embraced in India, but it is part of the Personal Data Security Bill Draft, 2018.